The effect of consumer rights awareness on attitude and purchase intention in the hotel industry: Moderating role of demographic characteristics - Charles Makanyeza; Tendai Douglas Svotwa; Olumide Olasimbo Jaiyeoba (Cogent Business & Management, 2021)
This study examines the effect of consumer rights awareness on consumer attitude and consumer intention, the effect of consumer attitude on consumer intention, and the moderating effects of gender, age and education on the effect of consumer rights awareness on both consumer attitude and intention. Using data from a sample of 366 hotel guests, the study employs structural equation modelling and moderated regression analysis to test the research hypotheses. Results indicate that consumer rights awareness has a positive effect on both consumer attitude and intention while consumer attitude has a positive effect on consumer intention. Results further indicate that education moderates the effect of consumer rights awareness on both consumer attitude and intention while gender and age do not. The study is among the pioneers to examine the effect of consumer rights awareness on both consumer attitude and behavioural intention and to test the moderating effects of demographic characteristics on these relationships.
Keywords: 650; Consumer action; consumer attitude; consumer intention; consumer rights; consumer rights awareness; knowledge of consumer rights